Labeling of chordal rings - Javaid, Imran; Ismail, Abida; Salman, Muhammad; Ahmad, Ali; Slamin (Utilitas Mathematica, 2013)
The chordal ring of order n,denoted by CRn(x,y,z),is the graph with vertex set Zn,an additive group of integers modulo n,and adjacencies given by i ∼ i + x,i ∼ t + y,i ∼ i + z for all even vertex i and distinct odd integers a;,y,z in [1,n-1]. In this paper,we provide super vertex-magic total labeling of CRn(1,3,5),n = O(mod 4)and(a,d)-antimagic labeling of CRn(1,3,7),n = 0(mod 4).